Effectiveness of Earthquake-Resistant Housing Training in Enhancing Disaster Mitigation Understanding among Vocational School Teachers - Laras Oktavia Andreas; Fitra Rifwan; Agri Americo Agamuddin; Fani Keprila Prima; Annisa Prita Melinda (Jurnal Pendidikan Teknik Sipil, 2025)
Background: Several studies indicate that teachers still have limited comprehension of reinforcement detailing, structural behaviour, and the application of SNI 1726:2019 and SNI 2847:2019. These limitations highlight the need for practical, hands-on training that strengthens both conceptual knowledge and technical construction skills, particularly for simple residential structures that frequently experience seismic damage. Methods: This study employed a descriptive qualitative approach to analyse the implementation and results of socialization activities and training on earthquake-resistant housing for teachers in the construction and property engineering department at SMK Negeri 1 Padang. Data collection was conducted through direct conceptual socialization, documentation, cici4d and participant engagement notes. The training consisted of conceptual socialization, demonstrations of the use of structural teaching aids such as a type 36 house model and reinforcement assemblies, hands-on practice, and field simulations designed to connect theoretical concepts with real-world practice. Results: The result of this study indicates that the practice-oriented training model is a valuable strategy to improve the competence and teaching skills of vocational teachers in earthquake-resistant housing construction and is proven to be effective in strengthening their contribution to disaster mitigation efforts. Conclusion: The training activity significantly improved teachers’ understanding of building structural components, reinforcement techniques, and basic load flow mechanisms in earthquake-resistant housing construction. Teachers’ active involvement in concepts and enabling them to apply construction principles in accordance with SNI. The collaborative learning environment provided a platform for the exchange of experiences among cici4d teachers, and field simulations also strengthened the connection between theoretical understanding and field processes.